Prenatal Detection of Silver–Russell Syndrome: A First Trimester Suspicion and Diagnostic Approach - Slavyana Galeva; Giuliana Diglio; Boris Stoilov; Ekaterina Uchikova; Lucian Pop (Medicina)
Background and Objectives: Silver–Russell Syndrome (SRS) is a rare genetic disorder characterized by prenatal and postnatal growth restriction, distinctive facial features, and body asymmetry. Early suspicion during the first trimester remains challenging but crucial for optimizing clinical outcomes. This study aims to highlight a diagnostic approach to the early suspicion of SRS. Materials and Methods: A 28-year-old primigravida presented for routine first-trimester prenatal care. An ultrasound revealed asymmetric growth restriction with normal anatomical findings. The first-trimester biochemical markers, including PAPP-A and β-hCG, were within the normal range. A further evaluation, including amniocentesis and genetic testing, was performed. Results: Genetic testing identified hypomethylation at the 11p15 imprinting control region, confirming the diagnosis of SRS. Parental testing excluded the maternal uniparental disomy of chromosome 7, suggesting an epigenetic mechanism. The findings were consistent with a clinical diagnosis of SRS, and appropriate counseling and multidisciplinary management were initiated. Conclusions: This case underscores the importance of the early recognition of atypical growth patterns, the integration of advanced genetic testing, and multidisciplinary counseling to guide parental decision-making and improve outcomes.